ANALISIS KUALITAS AIR DAN ESTIMASI POTENSI BEBAN PENCEMARAN PADA SUNGAI BATANG ARAU, KOTA PADANG - Adnan Sabilil Khairi Salfia; Widya Prarikeslan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The objectives of this study are: (1) Analyse water quality and determine the status of water quality in the Batang Arau River, Padang City by considering several physical (temperature, TDS, TSS,), chemical (BOD, COD, DO, total phosphate (T-Phosphate), pH, nitrate (NO3-N), ammonia (NH3-N) and biological (fecal coliform) parameters. (2) Estimating the potential pollution load of Batang Arau River from domestic, industrial and agricultural sectors. This type of research is descriptive quantitative. There are 2 methods used in this research, in analysing water quality and identifying water quality status using the STORET method. Meanwhile, to estimate the potential pollution load in Batang Arau River, this research uses an indirect calculation by calculating the potential pollution load sourced from the 2017 Citarum River Pollution Load Capacity and Allocation book. Determination of sample points using purposive sampling technique with a total of 5 sample points spread from upstream to downstream. The results showed that (1) Based on the analysis results, 7 out of 11 water quality parameters experienced problems including temperature, TDS, BOD, COD, DO, T-Phosphate and Ammonia. The quality status of the Batang Arau River at sample points 1 and 2 is still categorised as meeting quality standards, sample 3 is classified as mildly polluted, samples 4 and 5 are categorised as heavily polluted. (2) The highest potential pollution load in the Batang Arau River is caused by the domestic sector, followed by the industrial and agricultural sectors. The ability to accommodate the pollution load in the Batang Arau River is influenced by the amount of river water discharge and water quality, high water discharge accelerates the process of dissolving pollutants in water through the process of self purification.